2017
DOI: 10.1590/s0100-83582017350100075
|View full text |Cite
|
Sign up to set email alerts
|

Biological Control of Charcoal Rot of Mungbean by Trichoderma harzianum and Shoot Dry Biomass of Sisymbrium irio

Abstract: -A pot experiment was carried out for the biological control of charcoal rot on mung bean (Vigna radiata), caused by Macrophomina phaseolina. Pot soil was made sick with an inoculum of M. phaseolina. Dried powdered leaves of Sisymbrium irio, a weed from the Brassicaceae family, were mixed in soil at 1, 2 and 3% (w/w) with and without the application of Trichoderma harzianm, a fungal biological control agent. The highest grain yield (3.62 g pot -1 ) was recorded in a combined application of T. harzianum and 1% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Results of the present study showed that when either T. harzianum or T. viridi were used in combination with 3% dry biomass of C. album, the effect on plant growth and yield was same as that of application of 3% dry biomass alone. By contrast, recently Javaid et al (2017) reported that application of dry biomass of a brassicaceous weed Sisymbrium irio in combination with T. harzianum gave significantly higher crop growth and yield of mung bean when compared to application of either alone. In the present study, individual application of either T. harzianum or T. viridi significantly enhanced crop growth and yield under stress of S. rolfsii.…”
Section: Resultsmentioning
confidence: 79%
“…Results of the present study showed that when either T. harzianum or T. viridi were used in combination with 3% dry biomass of C. album, the effect on plant growth and yield was same as that of application of 3% dry biomass alone. By contrast, recently Javaid et al (2017) reported that application of dry biomass of a brassicaceous weed Sisymbrium irio in combination with T. harzianum gave significantly higher crop growth and yield of mung bean when compared to application of either alone. In the present study, individual application of either T. harzianum or T. viridi significantly enhanced crop growth and yield under stress of S. rolfsii.…”
Section: Resultsmentioning
confidence: 79%
“…Many synthetic fungicides have shown promising results in severe disease infected areas but their application has recently been restricted because of pathogen resistance, pesticide residue, phytotoxicity, human health hazards, and environmental pollution (Mitrani et al, 2018). In this context, biological control based on beneficial microorganisms as well as natural plant products are used as eco-friendly approaches that can provide promising alternates to overcome the spread of charcoal rot pathogen of mungbean (Banaras et al, 2020;Javaid et al, 2017Javaid et al, , 2018. Several antagonistic fungi are available for the control of soil-borne fungal pathogens (Ali et al, 2020;Bisutti et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Trichoderma spp. act as biocontrol organisms and also stimulate the plant resistance and growth resulting in overall improvement in yield (Javaid et al 2017;. The biocontrol activity related to antibiotics and mycoparasitism also improves defense response or systemic resistance in plants (Naher et al 2014).…”
Section: Introductionmentioning
confidence: 99%